Fermentative production of β-Carotene from sugarcane bagasse hydrolysate by Rhodotorula glutinis CCT-2186 - Díaz-Ruiz, Erick; Balbino, Thércia R.; dos Santos, Júlio C.; Kumar, Vinod; da Silva, Silvio S.; Chandel, Anuj Kumar (Springer, 2023)
Β-Carotene is a red–orange pigment that serves as a precursor to important pharmaceutical molecules like vitamin A and retinol, making it highly significant in the industrial sector. Consequently, there is an ongoing quest for more sustainable production methods. In this study, glucose and xylose, two primary sugars derived from sugarcane bagasse (SCB), were utilized as substrates for β-carotene production by Rhodotorula glutinis CCT-2186. To achieve this, SCB underwent pretreatment using NaOH, involved different concentrations of total solids (TS) (10%, 15%, and 20%) to remove lignin. Each sample was enzymatically hydrolyzed using two substrate loadings (5% and 10%). The pretreated SCB with 10%, 15%, and 20% TS exhibited glucose hydrolysis yields (%wt) of 93.10%, 91.88%, and 90.77%, respectively. The resulting hydrolysate was employed for β-carotene production under batch fermentation. After 72 h of fermentation, the SCB hydrolysate yielded a β-carotene concentration of 118.56 ± 3.01 mg/L. These findings showcase the robustness of R. glutinis as a biocatalyst for converting SCB into β-carotene.
Keywords: Sugarcane bagasse; Pretreatment; Enzymatic hydrolysis; Rhodotorula glutinis; Fermentation; β-Carotene